Reducing stigma toward autistic peers: a pilot investigation of a virtual autism acceptance program for children - Davidson, Denise; Morales, Dakota (Frontiers in Psychiatry, 2023)
Inclusive educational practices can be beneficial for autistic children, especially when the general education classroom can better meet the child's academic and socio-emotional needs than a special education classroom. Unfortunately, autistic children may not thrive in general education classrooms if they are perceived negatively, subject to bullying, and are socially isolated and rejected by their typically developing peers. Autism acceptance programs may help address the root cause of these problems, autism stigma. Thus, this study evaluated the effectiveness of a virtual autism acceptance program presented to typically developing, 8-to 10year-old children through remote learning technology. The five-week, stakeholder-approved pilot program included a themed module each week (e.g., facts about autism and reducing stigma, sensory sensitivities, strengths of those with autism) presented through a variety of online educational materials. Pretest, posttest, and maintenance results showed that the program was effective in improving children's knowledge about autism, and children's attitudes and behavioral intentions towards their peers with autism. In addition to reducing autism stigma, study findings suggest that remote learning and virtual tools can be used to implement an efficacious autism acceptance program to children, allowing for greater and more cost-effective outreach to children and schools.